Futile xylitol cycle in Lactobacillus casei. - Hausman, S Z (1984)
A futile xylitol cycle appears to be responsible for xylitol-mediated inhibition of growth of Lactobacillus casei Cl-16 at the expense of ribitol. The gratuitously induced xylitol-specific phosphoenolpyruvate-dependent phosphotransferase accumulates the pentitol as xylitol-5-phosphate, a phosphatase cleaves the latter, and an export system expels the xylitol. Operation of the cycle rapidly dissipates the ribitol-5-phosphate pool (and ultimately the energy supply of the cell), thereby producing bacteriostasis.